Current status and influencing factors of family resilience in families of children with epilepsy: a cross-sectional study - Wei, Wenjing; Dong, Lianlian; Ye, Jinghua; Xiao, Zhitian (Frontiers in Psychiatry, 2024)
Purpose The study was designed to describe the level of family resilience and identify the protective factors and vulnerability factors of family resilience in families of children with epilepsy. So as to provide theoretical guidance for implementing intervention programs to promote family resilience. Methods From November 2020 to July 2021, 258 parents of children with epilepsy were investigated using a convenience sampling method. The questionnaire included demographic data, Chinese-Family Resilience Assessment Scale, Social Support Rating Scale, and the Beck Depression Inventory. SPSS25.0 was used for descriptive statistical analysis, univariate analysis, and multivariate linear regression analysis. Results In this study, two hundred and fifty-eight primary caregivers completed the paper questionnaires. The total score of family resilience was (134.97 ± 16.57), which was above the medium level. Multiple linear regression analysis revealed that subjective support (β=0.327, P<0.001), comorbidity (β=0.181, P<0.05), objective support (β=0.117, P<0.05), and parental depression (β=-0.158, P<0.05) were significantly related to family resilience. These variables contribute 31.7% of the variance in family resilience (F=18.07, P< 0.001). Conclusion The families of children with epilepsy presented appropriate resilience after the children were diagnosed with epilepsy. Family resilience was correlated with multiple factors, subjective and objective support could be protective factors, comorbidity and parental depression could be vulnerability factors of family resilience. Therefore, future psychosocial interventions could focus on enhancing subjective support and objective support, reducing parental depression, and screening for epilepsy comorbidity to promote the family resilience of children with epilepsy.